Microwave Assisted Hydrodistillation - An Overview of Mechanism and Heating Properties - Nitthiyah, Jeyaratnam; Nour, A. H.; K., Ramesh; Akindoyo, John Olabode (AENSI Publishing, 2017)
The efficiency of heating mechanism of microwave assisted hydrodistillation (MAHD) in the extraction of essential oil is presented. The theoretical study on the microwave heating mechanism is also reported in terms of dielectric properties, volume rate of heat generation and penetration depth. MAHD extraction method has the advantages of being rapid, less solvent consuming, environmental friendly and green technology. Detailed information on the heating mechanism of MAHD is therefore presented herein alongside the potential of MAHD.